2010
DOI: 10.1115/1.3204532
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Forced Flame Response of Swirl-Stabilized Turbulent Lean-Premixed Flames in a Gas Turbine Combustor

Abstract: Flame transfer function measurements of turbulent premixed flames are made in a model lean-premixed, swirl-stabilized, gas turbine combustor. OH∗, CH∗, and CO2∗ chemiluminescence emissions are measured to determine heat release oscillation from a whole flame, and the two-microphone technique is used to measure inlet velocity fluctuation. 2D CH∗ chemiluminescence imaging is used to characterize the flame shape: the flame length (LCH∗ max) and flame angle (α). Using H2-natural gas composite fuels, XH2=0.00–0.60,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(21 citation statements)
references
References 26 publications
2
17
0
2
Order By: Relevance
“…The outer flame front in the OSL can clearly be identified in both images leading to an M flame shape. As suggested in [3] , the increase in laminar burning velocity S 0 l due to the increase of X fuel H 2 helps the reaction zone to propagate upstream through the OSL. The presence of the outer flame front in the OSL also depends on the stretch limit which is strongly extended when the Lewis number of the combustible mixture decreases [6] as it is the case when the fuel is enriched with hydrogen [46,47] .…”
Section: Impact Of Fuel Composition On the Flame Topologymentioning
confidence: 85%
See 1 more Smart Citation
“…The outer flame front in the OSL can clearly be identified in both images leading to an M flame shape. As suggested in [3] , the increase in laminar burning velocity S 0 l due to the increase of X fuel H 2 helps the reaction zone to propagate upstream through the OSL. The presence of the outer flame front in the OSL also depends on the stretch limit which is strongly extended when the Lewis number of the combustible mixture decreases [6] as it is the case when the fuel is enriched with hydrogen [46,47] .…”
Section: Impact Of Fuel Composition On the Flame Topologymentioning
confidence: 85%
“…The shape taken by the flame then affects the temperature field in the burnt gases at the outlet of the combustion chamber and pollutant emissions. Experiments and simulations indicate that the topology of swirling flames is highly sensitive to fuel composition [3][4][5] and heat transfer to the combustion chamber walls [6][7][8][9][10] . Simulations of the stabilization regimes of these flames are very challenging as numerous physical phenomena such as the combustion chemistry, flame interactions with turbulence, and heat losses have to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the net effect of H 2 addition on NO x formation is determined by the combined effects. Studies focused on the flame structures and combustion oscillations showed that the use of H 2 significantly altered the flame characteristics due to the different properties of transport and chemical reactivity [18,19]. Some investigations with a swirl-stabilized configuration indicated that the thermoacoustic instabilities were very sensitive to the H 2 molar fraction in the fuel blends [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For S 0 = 0.70, combustion is more compact and takes place closer to the injector rim, but the flame switches intermittently between a V-shape stabilized at the burner outlet and a lifted pattern far away from the burner. Between 0.75 ≤ S 0 < 0.95, the flame takes a well defined Vshape [11,34] with a flame leading edge lying above the burner outlet z f > 0. Figure 3(c) shows the reference flame obtained for S 0 = 0.85 that will be further examined with PIV and OH-PLIF diagnostics.…”
Section: Flame Stabilizationmentioning
confidence: 99%